1998
DOI: 10.1002/(sici)1099-1573(199811)12:7<484::aid-ptr341>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of the methanol extracts from compositae plants on 12-O-tetradecanoylphorbol-13-acetate-induced ear oedema in mice

Abstract: We report that the extracts of Compositae plants inhibit 12‐O‐tetradecanoylphorbol‐13‐acetate (TPA)‐induced ear oedema in mice. Seventy five methanol extracts obtained from 53 species in 11 tribes of Compositae plants were assayed and their inhibitory ratios calculated. In general, medicinal and edible plant extracts were more effective inhibitors than those from other materials, and the flower extracts were more effective inhibitors than those from other parts. The methanol extracts of the flowers of Cirsium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In an earlier study, the triterpene uvaol isolated from dried flowers of Taraxacum platycarpum inhibited the TPA-induced inflammation almost equivalent to that of indomethacin with 0.1 mg/ear being the 50% inhibitory dose (Yasukawa et al, 1996). Extracts of Taraxacum officinale leaf and roots exhibited slightly lower inhibition rates of 69 and 51%, respectively, in the same assay (Yasukawa et al, 1998). Kim et al (2000) studied the effect of a Taraxacum officinale leaf extract on the production of tumor necrosis factor alpha (TNF-␣) from primary cultures of rat astrocytes stimulated with substance P and lipopolysaccharide.…”
Section: Choleretic Activitymentioning
confidence: 99%
“…In an earlier study, the triterpene uvaol isolated from dried flowers of Taraxacum platycarpum inhibited the TPA-induced inflammation almost equivalent to that of indomethacin with 0.1 mg/ear being the 50% inhibitory dose (Yasukawa et al, 1996). Extracts of Taraxacum officinale leaf and roots exhibited slightly lower inhibition rates of 69 and 51%, respectively, in the same assay (Yasukawa et al, 1998). Kim et al (2000) studied the effect of a Taraxacum officinale leaf extract on the production of tumor necrosis factor alpha (TNF-␣) from primary cultures of rat astrocytes stimulated with substance P and lipopolysaccharide.…”
Section: Choleretic Activitymentioning
confidence: 99%
“…A review (Rahman and Zaman, 1989) summarizing the literature on the anti-diabetic activity of 343 medicinal plants in the indigenous system of medicine was carried out. Plants such as Adhatoda vasica (Claeson et al, 2000), Abies pindrow (Singh and Pandey, 1997;Singh et al, 2000), Artemisia roxburghiana (Bicchi et al, 1998), Bauhinia variegata (Sharma and Saxena, 1996), Centaurea iberica (Shamyanov et al, 1998), Cassia fistula (Agarkar and Jadge, 1999), Euphorbia helioscopia (Park et al, 2001), Morus alba (Chen et al, 1995), Taraxacum officinale (Yasukawa et al, 1998) and Peganum harmala (Lamchouri et al, 1999) have extensively been investigated. Various chemical constituents have been isolated from these plant species, so we decided to select the only plant species or the part of the plant, which have not been previously investigated for secretagogue activity.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 Ukiya et al found that methanol extracts of HAF markedly inhibited TPAinduced inflammation in mice. 40,42 Here, we hypothesized that HAF possesses photoprotective ability against UVBinduced damage. As expected, our results demonstrated that HAF effectively reversed UVB-induced photoaging by inhibiting MMP secretion and procollagen type I reduction, which were involved in inactivating MAPK/AP-1 and upregulating TGF-β expression.…”
Section: Discussionmentioning
confidence: 99%